Coaching winning Model United Nations teams : a teacher's guide - Mickolus, Edward F. (Potomac Books Inc., 2013)
By some counts, Model United Nations (MUN) has become the single most popular extracurricular academic activity among high school students. More than two million high school and college students have assumed the roles of ambassador from real United Nations member countries, participated in spirited debate about the world's most pressing issues, and called, "Point of order, Mr. Chairman!" In this book, the authors give MUN teachers and coaches the information they need to succeed - before and during a conference.